The Effectiveness of Brainstorming Strategy in Teaching Philippine Politics and Governance - Araňa, Kenna Mary; Magbanua-Claur, Annabee (Technium Social Sciences Journal, 2022)
Brainstorming is a decision-making strategy that can be used in any setting where people are expected to participate.This quasi-experimental research aimed to assess the effectiveness of brainstorming strategy in teaching Philippine Politics and Governance to fifty (50) Grade 12 students of San Miguel National High School in La Carlota City for the School Year 2018-2019. The statistical techniques used in determining its effectiveness were the mean, standard deviation, t-test, and ANCOVA. Analyzed data revealed no significant difference in the pre-test scores of both the experimental and control groups. Furthermore, there is a significant difference in the experimental and control groups’ pre-test scores and post-test scores. The results likewise proved no significant difference in the experimental and control groups. Thus, the study has an immediate implication for teachers and practitioners who attempt to find alternative teaching-learning methods. Also, teachers may use brainstorming strategies in the absence of technology.